The Role of Marketing Mix Strategies on Brand Loyalty of Cable Products - Weldemariam, Tizitaye; Ayele, Yibeltal Nigussie (Asian Business Review, 2020)
This study was carried out with the intention of examining the role of the marketing mix on brand loyalty advertising and pricing play in building brand equity. The study focuses on a new cable brand (Belayab Cable) and attempts to find out the role of marketing mix elements on brand loyalty of Belayab Cable products. For this study, an accessible population of 62 Belayab Cable consumers who have used its products at least twice was selected randomly from stratified groups of three types of customers (Contractors, Traders, Electo Mechanical Engineers, and Government,). A structured questionnaire was used to collect data from respondents by using a self-administered data collection system. In addition to the questionnaire, semi-structured interview questions are prepared to get information from the organization which is analyzed qualitatively. The STATA is used to process the primary data which were collected through questionnaires. The findings showed that the role of product quality, price, and availability has a positive and significant role in brand loyalty. On the other hand, the price has no significant role in brand loyalty for the cable of a brand. Therefore, in order to maximize the effectiveness of marketing activities and have more loyal customers in cable industry companies should pay more attention to product quality, availability, and promotions.